Professional Skepticism And Auditors' Judgments: Evidence from Tunisia - Hager Ennar; Salma Damak-Ayadi (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What is the impact of professional skepticism on auditors' judgment across varying levels of control risk? Motivation- Professional skepticism has attracted the attention of various regulators, practitioners, and researchers. However, the empirical results of previous studies have not consistently yielded findings regarding the impact of professional skepticism on auditors' judgment. Idea- This paper aims to investigate the relationship between professional skepticism and auditors' judgment across different control risk scenarios within the Tunisian context. Data- The experimental study comprised 127 auditors. Tools- A between-subjects experiment was conducted, manipulating control risk at two levels (low and high risk). Hurtt (2010) professional skepticism scale was utilized to measure auditors' professional skepticism. Subsequently, a multivariate regression analysis was performed. Findings- The experimental study provided evidence that professional skepticism leads auditors to exhibit skeptical judgments regarding the assessment of the truthfulness of the client's explanation and the assessment of fraud risk. Additionally, the results show that auditors tend to make more skeptical judgments in a high-risk setting. Contribution- Understanding the role of trait professional skepticism is crucial for practicing auditors and accounting firms. The findings suggest that professional skepticism has a significant effect on auditors' judgment. Consequently, firms should pay particular attention to the allocation of audit team members based on their level of skepticism.
Keywords: M42; 650; professional skepticism; trait; judgment; Tunisia